1999
DOI: 10.1002/(sici)1521-3803(19991201)43:6<418::aid-food418>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp's waste: Chemical composition, nutritional value and utilization

Abstract: Shrimp's waste (dried head or shell) was found of high protein content and high level of minerals especially Ca, P, Na and Zn. The amino acids profile of the dried shrimp's shell proved to be of higher values than the shrimp's head. Glutamic acid was the abundant amino acid in both dried samples. The saturated: unsaturated fatty acids ratio was 1 : 1.63 for the dried shrimp's head and 1 : 1.51 for the dried shrimp's shell. The dried shrimp's shell and head appeared to be free from aflatoxines (B1, B2, G1 & G2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 5 publications
5
22
0
2
Order By: Relevance
“…The crude protein content obtained showed that the redspotted shrimp residues were rich in this component, in agreement with values reported in the literature. Ibrahim et al (1999) reported values of 47.75% and 47.43% protein in the heads and shells of Penaeus spp. shrimp.…”
Section: Thin-layer Chromatography (Tlc) Identification Of the Carotesupporting
confidence: 93%
See 1 more Smart Citation
“…The crude protein content obtained showed that the redspotted shrimp residues were rich in this component, in agreement with values reported in the literature. Ibrahim et al (1999) reported values of 47.75% and 47.43% protein in the heads and shells of Penaeus spp. shrimp.…”
Section: Thin-layer Chromatography (Tlc) Identification Of the Carotesupporting
confidence: 93%
“…These waste products are economically recoverable, because they have high-quality protein, chitin, minerals, carotenoids, such as astaxanthin, and lipids that are high in x-3 fatty acids. Thus there is great interest in developing alternative uses to generate value-added products from the waste (Shahidi et al, 1992;Ibrahim et al, 1999;Nargis et al, 2006;Assunção and Pena, 2007;Rødde et al, 2008). Astaxanthin (ASX) is a pigment belonging to the xanthophyll family, and is the major carotenoid in red aquatic animals such crustaceans, salmonids and other farmed fish feeds (Saito and Regier, 1971;Meyers and Bligh, 1981;Sachindra et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…The crude protein content obtained (31.3% ± 0.61) showed that the pink shrimp residues were rich in this component, in agreement with values reported in the literature. Ibrahim et al [24] reported values of 47.75% and 47.43% protein in the heads and shells of Penaeus spp. shrimp.…”
Section: Resultsmentioning
confidence: 99%
“…About 35-45% by weight of shrimp raw material is discarded as waste depending on the species and processing method applied (INFOFISH 1991). With increasing competition on world markets there is a need to develop value-added products from the waste material to help maintain the economic viability of the industry as well as reduce environmental pollution (Gildberg and Stenberg 2001) Shrimp head and shell generally contain good percentage of protein with balanced amino acid profile and minerals like Ca, P, Na and Zn (Ibrahim et al 1999). Recovery of protein fraction from the shrimp waste by enzymatic hydrolysis has been widely studied (Synowiecki and Alkhateeb 2000;Mizani et al 2005) which has advantages since accelerated hydrolysis allows for control of hydrolysis and thus minimizes undesirable reactions.…”
Section: Introductionmentioning
confidence: 99%